Depression and inflammatory arthritis are associated in both Western and Non-Western countries: findings from the World Health Survey 2002 - Apfelbacher, Christian; Herr, Raphael; Loerbroks, Adrian (Journal of psychosomatic research, 2017)
OBJECTIVES: Epidemiological studies have linked arthritis to depression. However, it remains unclear to what degree the association between arthritis and depression extends to low income countries and whether it can be replicated for inflammatory arthritis (IA). We aimed to address these knowledge gaps based on a large multi-national sample. METHODS: Cross-sectional data was drawn from the 2002 World Health Survey. IA was defined as reports of either a diagnosis or treatment of arthritis and morning stiffness for >30min. Self-reported depression was defined as positive if participants reported its prior diagnosis or treatment or if they were classified as suffering from a major depressive episode by a seven-item screening instrument. Multivariable logistic regression analysis was used to estimate odds ratios (ORs) and 95% confidence intervals (CI) for the entire sample and stratified by sex and continent. RESULTS: The odds of IA was 2.6-fold increased in those with depression compared to those without (OR=2.64, 95% CI 2.18-3.21) in the entire sample. This association was observed in both men (OR=3.06, 95% CI 2.19-4.27) and women (OR=2.50, 95% CI 1.95-3.21). Similar associations were found on the continent level, but were generally stronger for the Americas and Asia compared to Africa and Europe. CONCLUSIONS: Although our definition of IA was limited by the use of self-reported morning stiffness, this study suggests that there is a positive association between inflammatory arthritis and depression in Western and Non-Western countries, suggesting that this relationship represents a universal phenomenon.
Available online 1. December 2016
Gesehen am 02.07.2018